Clinical Characteristics and Diagnostic Challenges of COVID−19: An Update From the Global Perspective - Israfil, S. M. Hasan; Sarker, Md. Moklesur Rahman; Rashid, Parisa Tamannur; Talukder, Ali Azam; Kawsar, Khandkar Ali; Khan, Farzana; Akhter, Selina; Poh, Chit Laa; Mohamed, Isa Naina; Ming, Long Chiau (Frontiers in Public Health, 2021)
Clinical characteristics are very important for the correct diagnostic of diseases. The current review aimed to systematically summarize the global clinical characteristics of the COVID-19 patients and to identify their diagnostic challenges to help the medical practitioners for correct diagnosis and better management of COVID-19 patients. We conducted a systematic search in PubMed, Web of Science, Scopus, Science Direct and Google Scholar databases for original articles containing clinical information of COVID-19 published up to 7th May 2020. Two researchers independently searched in databases to extract eligible articles. A total of 33 studies from 8 different countries with 10728 case-patients were included for clinical characteristics. The most common clinical symptoms were cough 59.5%, fever 46.5%, fatigue 27.23%, and dyspnea 20.8%. The prominent laboratory findings were lymphocytopenia 56.6% (4135/7309), elevated levels of CRP 60.12%, aspartate aminotransferase 54.3%, LDH 43.6%, ESR 72.99%, serum ferritin 63%, IL-6 52% and prothrombin time 35.47%, and decreased levels of platelets 19.45%, eosinophils 59.0%, hemoglobin 41.5% and albumin 38.4%. CT scan of the chest showed an abnormality in 93.89% cases with bilateral lungs 70.9%, ground-glass opacity 47.36%, lesion in lung 97.1% and enlargement of lymph node 50.7%. The common comorbidities were hypertension, diabetes, obesity and cardiovascular diseases. The estimated median incubation period was 5.36 days and case fatality rate was 16.9%. Global feature on the clinical characteristics of COVID-19 obtained from laboratory tests and CT scan results will provide useful information to the physicians to diagnose the disease and better management of the patients as well as to address the diagnostic challenges to control the infection.